Diachrone und synchrone Aspekte von Personal-, Possessiv- und Demonstrativpronomina in der Slawia - Wonisch, Arno (Slavia Centralis, 2020)
.
Keywords: personal pronouns; possessive pronouns; demonstrative pronouns; Slavic languages; Old Church Slavic